Exploring the short-term influence of a proprietary oil extract of black cumin (Nigella sativa) on non-restorative sleep: a randomized, double-blinded, placebo-controlled actigraphy study - Mohan, M. E.; Mohan, Mohind C.; Prabhakaran, Prathibha; Syam Das, S.; Krishnakumar, I. M.; Baby Chakrapani, P. S. (Frontiers in Nutrition, 2024)
Background Nigella sativa (black cumin, or black seed) is popularly known as the seed of blessings in the Arab system of medicine. Though not widely recommended for sleep, a unique proprietary black cumin extract (BlaQmax®/ThymoDream™; BCO-5) has been shown to be helpful in the management of stress and sleep issues. Methods This randomized, double-blind, placebo-controlled trial aimed to investigate the efficacy of BCO-5 on the sleep quality of volunteers characterized with a self-reported non-restorative sleep disorder. Healthy male and female participants (n = 70), aged 18-65 years (BMI 22-28 Kg/m2) were randomized to either placebo or BCO-5 (n = 35/group). Both interventions were supplemented at 200 mg/day for seven days. Actigraphy and a validated restorative sleep questionnaire (RSQ-W) were used to monitor the influence of BCO-5 on sleep. Results Compared to placebo, BCO-5 significantly improved sleep quality, as evidenced by both intra-group and inter-group analyses of the actigraphy data. The relative improvements observed were sleep efficiency (7.8%, p < 0.001), total sleep time (19.1%, p < 0.001), sleep onset latency (35.4%; p < 0.001), and wake-after-sleep-onset (22.5%; p < 0.001) compared with placebo. BCO-5 also improved sleep by 75.3% compared to baseline (p < 0.001) and by 68.9% compared to placebo (p < 0.001), when monitored by RSQ-W. BCO-5 was well-tolerated with no reports of side effects or toxicity. Conclusion BCO-5 significantly improved non-restorative sleep in seven days, indicating its potential role as a natural sleep aid.